The petrography and major element geochemistry of the phosphorite nodule deposits on the Agulhas Bank, South Africa - Parker, Robin James (Department of Geological Sciences, 2016)
Dredging operations carried out on the Agulhas Bank have proved the existence of a widespread phosphorite nodule deposit, considered to be essentially in situ. The pebble to boulder sized nodules recovered have been classified into two conglomeratic and three non-conglomeratic classes. The latter classes comprise (i) phosphatized microfossiliferous limestones (N I class); (ii) phosphatized highly ferruginous microfossiliferous limestones (N II class); and (iii) nodules composed of a poorly sorted mixture of quartz, glauconite and microfossil grains set in a micrite/collophane cement (N III class). Surface to centre phosphatization effects have been observed in some N I nodules. The first conglomeratic variety (C I class) is noted for abundant, often highly irregularly shaped, enclosed N I class phosphorite pebbles set in a matrix that is similar to the N III phosphorite type. The second conglomeratic variety (C II class) is similar to the first, but it is characterised by the inclusion of pebble sized microfossiliferous internal cast of macrofossils, as well as the presence of macrofossil shell debris. X-Ray diffraction studies have shown that the prime phosphate mineral present is francolite, a carbonate fluorapatite, while optically this mineral has been identified as cellophane. An X-Ray diffraction peak-pair technique has indicated an average 5.5% CO₂ concentration in the apatite phase of the phosphorites. Studies on the major element geochemistry of the various phosphorite classes has shown that the bulk geochemistry of the nodules corresponds to the dominant mineralogy and that variations in the bulk geochemistry of the nodules from within a given group reflects variations in the concentration of diluent allogenic minerals. A sympathetic relationship exists between the Na and S concentrations in the phosphorites, and this has been related to substitution effects in the phosphate mineral phase. The average P₂O₅ concentration determined for the Agulhas Bank phosphorites is 16.18%. The N I and N II phosphorite classes are considered to have originated as a result of limestone phosphatization involving a calcite-to-francolite replacement process. Many of the sedimentological features exhibited by the texturally heterogenous N III, C I and C II class nodules are incompatible under normal hydrodynamic conditions, suggesting an unusual depositional environment. In order to explain these features it has been proposed that the nodules were originally lime mud rich sediments and that the conglomeratic varieties were deposited by submarine transporting agencies such as mud-flows, turbidity currents and/or tidal/storm wave surges. Bioturbation may have been responsible for the mixing of lime mud and coarser material to produce the poorly sorted non-conglomeratic N III phosphorite class. Replacement of the calcitic lime mud by francolite .s considered to be the prime mechanism responsible for the phosphate mineralization and lithification of these N III, C I and C II class phosphorites.